RETRACTED ARTICLE: Some quality attributes of heat-moisture treated water yam (Dioscorea alata) starch - H.K. Tiamiyu; J.M. Babajide; S.A.O. Adeyeye (Cogent Food & Agriculture, 2017)
This study investigated the effect of autoclave and oven heat-moisture treatment on some quality attributes of water yam starch. The water yam starch was adjusted to moisture content of 15–35% and subjected to heat-moisture treatment (HMT) using autoclave (at 120°C for 1 h) and oven (at 120°C for 12 h). Physicochemical, functional and thermal properties of the modified starches formed were carried out. Increase in amylose and resistant starch content of the samples occurred after the treatment. The water and oil absorption capacities also increased after HMT from 74.40 to 135.46% and 0.65 to 1.37 ml/g respectively. Swelling power was reduced while the solubility increased compared to native starch. Pasting time and temperature increased after HMT. A reduction in peak viscosity (643.03–80.82 RVU), trough (441.33–65.79 RVU), breakdown (203.13–93.58 RVU), and final viscosity (549.29–112.75 RVU) and set back (108.17–40.17 RVU) was noticed. Moisture content above 15% resulted in biphasic endotherms in both treatments, T0, Tp, Tc and Tc−T0 also increase. The temperature of the heating medium was found to affect the RS content of the starches.